PENGEMBANGAN SISTEM INFORMASI PENDANAAN SUMBER DAYA MANUSIA MENGGUNAKAN GOOGLE APPS SCRIPT - S, Syafnides Wulan; Dirgahayu, Teduh (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
Human Resource (HR) development is a key element in improving the quality of institutions, whether in the education sector or other organizations. However, manual management of HR funding can lead to errors in budget allocation and process delays. This research aims to develop an information system that automates the HR funding management process using Google Apps Script (GAS). GAS was chosen for its ability to integrate with Google Workspace services, facilitating automation and providing more transparent access to budget management. The system is also designed to simplify the management and manipulation of data directly from Google Sheets. The method used is the waterfall model, which includes the stages of requirements analysis, system design, implementation, and testing. The results show that the system can accelerate the funding submission and approval process, reduce human errors, and improve transparency as well as real-time monitoring of submission status. In conclusion, this information system was developed using Google Apps Script with the Vue.js, Bootstrap, HTML, and CSS frameworks, following the waterfall method. The system is expected to enhance efficiency and transparency in HR funding management across various organizations.